(untitled) (Journal of Nuclear Technology in Applied Science, 2020)
The present study was conducted to determine the effect of baits containing nano particles of silica against the fourth instar larvae of Agrotis ipsilon (Hufn.) along sequential daily intervals post treatment under laboratory conditions. The determined percentages of larval mortality due to the admixed baits with SiNPs increased up to 100% after 15 days of application. The admixing of nanoparticles of silica in the bait during the sensitive period of larval development caused morphological abnormalities that are generally irreversible and often lead to death, beside certain biochemical changes of some inorganic elements in the haemolymph of the treated insects. It could be concluded that the tested nanoparticles of silica were most effective and indicated the highest concentration reductions of inorganic constituents in larval haemolymph, especially calcium, sodium and potassium.Therefore, more attention must be directed towards the inorganic constituents in the larval haemolymph as biomarkers for SiNPs efficacy.